From Neighbourhood to Bioregion: The City as a Living System (2018)
The Greek physician Hippocrates described the effects of “airs, waters, and places” on the health of individuals and communities. For a short period, the industrial age distracted us from this whole-systems understanding of the world–but we are now learning again to think of cities as habitats, and as ecosystems, that co-exist on a single living planet. Humanising the city in this context-making it healthy for people–therefore means making it habit- able for all of life, not just human life. It means thinking of the city as a local living economy, not as a machine. And it means the embrace of biodiversity, and local economic activity, as better measures of a city’s health than the amount of money that flows through it. The notion of the city as a living system generates cultural energy, too: A narrative based on caring–for each other, and for our places–creates the meaning and shared purpose we’ve been so badly lacking.